Pengembangan PowerPoint Interaktif “SAHIBINAH” (Kisah Hijrah Nabi Muhammad ke Madinah) pada Pembelajaran PAI Kelas IV SD - Ummi Muthi’ah Zaujaha; Siti Patimah; Dwi Zahra Aulia; Ani Nur Aeni (Departement of Mathematics Education, 2024)
This research was carried out because of the learning problems in students in grade four elementary school regarding difficulties in remembering material and lack of enthusiasm when the learning process takes place. This is because the learning method used is still fixated on the teacher, namely using the lecture method. Therefore, the researcher intends to prove the effectiveness of interactive PowerPoint learning tools in learning. The system determined regarding this study is the Design and Development (D&D) method using the ADDIE development model. The research sample is grade 4 of SDN Palasari, with a total of 8 students. The material provided is about